Hymer and Public Policy in LDCs - Lecraw, Donald J. (American Economic Review, 1985)
Initially this paper was titled, Stephen Hymer's Influence on Public Policy in LDCs. In an attempt to research this impossible subject, I conducted a citation search in the SSCI. The SSCI listed 442 citations in 192 different journals over the period 1977 to 1983, a count that places Hymer in the top five writers on international business and the multinational enterprise over that period. His writings were cited in journals devoted to law, history, philosophy, sociology, psychology, political science, geography, business, anthropology, broadcasting, peace research, statistics, migration, and urban, regional, agricultural, trade, financial, labor, industrial, and development economics; they were cited in journals devoted to the study of Africa, Asia, Latin America, as well as Europe, Australia, New Zealand, and North America; and they were cited by authors across the spectrum from arch conservative to radical political economists. The breadth of discipline, geography, and viewpoint of the authors who found Hymer's writings useful in their analysis reflects Hymer's multidisciplinary approach to problems, the originality of his insights, the clarity of his thought, and the forcefulness of his writing. Although Hymer is best known for his work on the multinational enterprise (MNE), he also was intensely concerned with problems of less developed countries (LDCs) and the public policies they might use to alleviate the problems arising from trade and foreign direct investment (FDI). In his analyses, Hymer started from his base in economics, especially the economics of the MNE, but also used the insights of historical, political, and sociological analysis to illuminate these complex subjects. In using this approach Hymer may have fallen between two camps in the analysis of public policy issues in LDCs: the pure economists (who have often viewed him as a bright, but misguided and ultimately fallen angel) on the one side, and the radical political economists (who have viewed him as a rising, if somewhat backward star) on the other side. Instead of bridging the gap, Hymer may have fallen into it: his insights cited, but his conclusions discounted as faulty or half-formed. This is unfortunate, since Hymer, writing in the 1960's and early 1970's, speaks directly to many of the concerns of today and of the future: the New International Economic Order, the North-South dialogue, and the basic needs of those at the bottom of the income distribution in high-income and lowincome countries alike. Hymer's writings addressed two major questions: how best should a small, developing country interact with the world economy through trade, inward (and outward) FDI, and technology licensing? How best should such a country organize its internal economic activity to meet the needs of all its people, especially those in the lower two-thirds of the income distribution? To understand Hymer's approach to the analysis of these two questions and his contribution to public policy in LDCs, it is useful to set them within the context of his background, education and experience. Hymer was a Canadian. He grew up and received his first university degree in Canada, a country with a small, open economy, which largely exports raw materials and imports manufactured products, and whose manufacturing, energy, and mining sectors are dominated by subsidiaries of MNEs. In many ways, Canada was (and is) akin to the LDCs and his interests naturally turned in their direction. He was educated as an industrial organization economist at McGill and MIT. His experience and education, therefore, gave him a knowledge of large, multinational enterprises and the tools to analyze them. After MIT, Hymer worked in Ghana where he saw * Professor, School of Business Administration, University of Western Ontario, London, Ontario, N6A 3K7 Canada. I am grateful for partial funding from the Centre for International Business Studies and the Fund for Excellence, U.W.O.